Pengaruh waktu aplikasi dan konsentrasi pupuk daun terhadap proses fisiologis dan pertumbuhan anggrek dendrobium = The effect of application time and concentration of foliar fertilizer on the physiological process and... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Foliar application increases growth of orchids. An experiment to study the effect of application times. and concentration of foliar application to physiological processes and gi'owth of ten month old dendrobium orchid has been done at Kotabaru, Yogyakarta, 113 m above sea level from February to July 2000. The design used was a 3x2 factorial, replicated three times. The fertilizers of concentration 2 ml/1 and 4 m1/1 were each applied in morning ( 10.00 am ), afternoon ( 05.00 pin) and at night ( 08.00 pm ). Observation were done for number and aperture of stomates opening, rate of transpiration, N concentration of leaves, water content of leaves, stem and roots, plant height, number of leaves, leaf area, leaf area ratio, specific leaf weight, net assimilation rate, and relative growth rate. Data were analyzed by analysis of variance and Duncan New Multiple Range Test at 5 % level of significance. Result of the experiment showed that orchid leaves stomates opened in afternoon and stayed up to night. The fastest rate of transpiration occured in the afternoon when stomates have already opened and atmospheric environments support this process. No significant effect of different times of foliar application on the nitrogen, content of leaves, but plants fertilized in afternoon or at night accumulated higher weight of nitrogen compared with those fertilized in the morning. No different effect of application in the afternoon and at night, and also no different effect of concentration was found.